2023
DOI: 10.3390/metabo13030423
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Analysis of Metabolome and Transcriptome Reveals Molecular Insight into Metabolomic Variations during Hawthorn Fruit Development

Abstract: Hawthorn (Crataegus pinnatifida var. major), a cultivated fruit tree, is native and unique to China. Its fruits have high nutritional, health, and medicinal values. However, the development and ripening process of hawthorns is accompanied by dramatic changes in flavor, aroma, and bioactive phytochemicals, which are the fundamental factors that contribute to the potential health benefits and establishment of fruit quality. Therefore, an exploration of the dynamic changes in metabolites and their regulatory netw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…Major N. E. Br. (family Rosaceae) is a fruit tree widely distributed in Asia, Europe, North Africa, and North America ( Wang et al, 2023a ; Wen et al, 2015 ). Its fresh ripe fruits are picked on, purified, sliced, and dried in the sunlight to obtain edible and medical hawthorn.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Major N. E. Br. (family Rosaceae) is a fruit tree widely distributed in Asia, Europe, North Africa, and North America ( Wang et al, 2023a ; Wen et al, 2015 ). Its fresh ripe fruits are picked on, purified, sliced, and dried in the sunlight to obtain edible and medical hawthorn.…”
Section: Introductionmentioning
confidence: 99%
“…Its fresh ripe fruits are picked on, purified, sliced, and dried in the sunlight to obtain edible and medical hawthorn. It has been reported that more than 150 bioactive substances, including flavonoids, phenolic acids, organic acids, lignans, terpenoids, and sugars, have been found in hawthorn, especially rich in flavonoids and phenolic acids ( Wang et al, 2023a ). As one of herbal raw material, hawthorn has been officially documented in Chinese, European, American, and Canadian Pharmacopeias ( Wang et al, 2023a ; Zureke al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonetheless, metabolomics is quickly becoming recognized as a crucial analytical approach in nutritional studies due to the essential role that metabolism plays in nutrition ( Ulaszewska et al., 2019 ; Shen et al., 2023 ). By qualitatively and quantitatively examining all of an organism’s metabolites, a technique known as “metabolomics” can be used to investigate dynamic changes in metabolites as well as accumulation patterns and the genetic bases of plant metabolites ( Shen et al., 2023 ; Wang et al., 2023 ). A revolutionary method called widely targeted metabolomics analysis allows for the simultaneous quantification of over 1000 known and unknown compounds in addition to hundreds of recognized metabolites ( Wang et al., 2018 ; Li and Song, 2019 ; Waris et al., 2022 ; Xue et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%